Adobe Dreamweaver CS6 : classroom in a book - Maivald, James J. (San Jose, CA : Adobe Press, 2012)
Covers the basics of learning Adobe Dreamweaver and provides countless tips and techniques to help you become more proficient with the program--
Getting started -- Customizing your workspace -- HTML basics -- CSS basics -- Creating a page layout -- Working with cascading style sheets -- Working with templates -- Working with text, lists, and tables -- Working with images -- Working with navigation -- Adding interactivity -- Working with web animation and video -- Working with forms -- Working with online data -- Building dynamic pages with data -- Publishing to the web -- Appendix: TinyURLs.
Keywords: Dreamweaver (Computer file); Web sites -- Authoring programs; Web sites -- Design; HTML editors (Computer programs)